J.E. Bernier’s Claims to Fame - MacEachern, Alan (Scientia Canadensis, 2010)
On 1 July 1909, in the course of patrolling the Arctic on behalf of Canada, Captain J.E. Bernier claimed for Canada the territory between its east and west mainland borders all the way to the North Pole—that is, the entire Arctic Archipelago. Although the legitimacy of his act was considered dubious even by his own government, it introduced the “sector principle” to international practice and has since become a staple in the nation’s claims to Arctic sovereignty. But focus on Bernier’s sector claim has obscured attention from his four voyages for Canada in the first decade of the century, and paradoxically left the broader context for his claim unexplored. This essay frames his 1909 act in relation to his decade-long quest to win fame as Canada’s competitor in the race to the North Pole. The article’s specific contributions are in revealing that Bernier actually made a sector claim during his previous cruise; that his connections in 1908 with American polar challengers Peary and Cook encouraged his 1909 decision; and that although the Dominion Day proclamation was what he would be remembered for, Bernier himself later ascribed surprisingly little significance to it.